Weight and skeletal muscle loss with cabozantinib in metastatic renal cell carcinoma. Issue 5 (28th July 2022) - Colomba, Emeline; Alves Costa Silva, Carolina; Le Teuff, Gwénaël; Elmawieh, Jamie; Afonso, Daniel; Benchimol‐Zouari, Axelle; Guida, Annalisa; Derosa, Lisa; Flippot, Ronan; Raynard, Bruno; Escudier, Bernard; Bidault, François; et al.
Abstract: Background: Cabozantinib, a standard of care metastatic renal cell carcinoma (mRCC), may be associated with weight and muscle loss. These effects of new generation VEGFR tyrosine kinase inhibitor on muscle mass loss are poorly described. Methods: All cabozantinib‐treated mRCC patients from January 2014 to February 2019 in our institution were included. Clinical data including weight were collected during therapy. Computed tomography images were centrally reviewed for response assessment, and axial sections at the third lumbar vertebrae were used to measure the total muscle area. Toxicities and cabozantinib outcomes were evaluated. Co‐primary endpoints included skeletal muscle loss and weight loss (WL), longitudinally evaluated during treatment. WL has been classified according to CTCAEv5.0: Grade 1 (loss of 5 to <10% of baseline body weight), Grade 2 (loss of 10% to <20% of baseline body weight), and Grades 3–4 (loss >20% of baseline body weight). Results: Patients were mostly men (70.3%), median age was 59.2 (range: 22.0–78.0) years, and median baseline body mass index was 25.0 (range: 16.4–49.3) kg/cm 2 . Prognosis according to International Metastatic RCC Database Consortium score was good, intermediate, and poor for 13 (13.0%), 63 (63.0%), and 24 (24.0%) patients, respectively. Out of a total of 120 patients, 101 patients with a median follow‐up of 22.3 months (range: 4.5–62.2) were eligible for analysis; 85 experienced muscle loss and muscle loss >10% increased during cabozantinib exposition, especially after 6 months of treatment. At cabozantinib baseline, 71 patients (70.3%) had sarcopenia, and 16/30 (53.3%) non‐sarcopenic patients developed sarcopenia during treatment. Baseline sarcopenia was associated with lower response rates ( P = 0.031) and higher grades 3–4 toxicities ( P = 0.001). Out of 92 patients included in the WL analysis, 44 (47.8%) and 12 (13.0%) experienced grades 2 and 3 WL, respectively. Conclusions: We report a high incidence of grades 3–4 WL, fourth times higher than reported in prior pivotal trials, and half of the patients developed sarcopenia while on cabozantinib treatment. Weight and muscle mass loss with cabozantinib are underreported and may require further investigations and early management.